Handbook of environmental engineering - Kutz, Myer (John Wiley & Sons, Inc., 2018)
2.1 Introduction; 2.1.1 Data Quality Objectives; 2.1.2 Monitoring Plan Example; 2.1.3 Selection of a Monitoring Site; 2.2 Environmental Sampling Approaches; 2.2.1 Sampling Approaches; 2.3 Laboratory Analysis; 2.3.1 Extraction; 2.3.2 Separation Science; 2.4 Sources of Uncertainty; 2.5 Measurements and Models; 2.6 Contaminants of Concern; 2.7 Environmental Indicators; 2.7.1 Oxygen; 2.7.2 Indices; 2.8 Emerging Trends in Measurement; 2.8.1 Sensors; 2.8.2 Big Data and the New Decision-Making Paradigm; 2.8.3 Biological Measurements; 2.9 Measurement Ethics; Note; References.